Declaration of original work / Mohamad Farizaman Syah Mohd Salleh, Muhammad Azim Masthooth & Mohammad Luthti Manah - Mohd Salleh, Mohamad Farizaman; Masthooth, Muhammad Azim; Manah, Mohammad Luthti (2015)
The Motor-Generator Self-looped with usable energy left Over is designed to see the function or effect motor-generator will be produce power to generate voltage. For this project, we expect this project succeeded in penetrating the market in the use of this technology. In addition, we expect this project is recognized as environmentally friendly and user friendly. Furthermore, the goal of this project is to reduce the use of electricity and reduce cost. The calculated parameters have been optimized using PROTEUS 8.1 software. The software can be using the simulation and PC 13 or schematic to run the result. The design prototype has been fabricated and the output was measured using Multimeter to analysis the final result. For the overall result we observed the energy will recycle power into mechanical to electrical and turn electrical to mechanical on the power of rotation motor to make the voltage. For this project, steps should be taken to start the function or operation of the project is starting from a 12 volt rechargeable batteries. Rechargeable batteries 12 volt will produce energy to motor and then motor will rotate. After that, the generator will produce electricity. When electrical energy produced from it generator, then will recycle to rechargeable batteries 12 volt. Rechargeable batteries 12 volt used as the main source and then distributed electrical energy to the power bank circuit. Lastly, the electrical energy will be deposited into the battery no 2(rechargeable batteries 6 volt) and energy out into the USB port. It is observed that the gain is improved when the motor-generator will functionally faster and smoothly to produce enough power